Middle Managers' Perspectives on Power Changes in Democratizing Organizational Transformations - Šimůnek, David (2025)
Importance - This dissertation examines how middle managers experience power changes within transformations that shift organizational design to more democratized structures. These changes redistribute rights and responsibilities and shift organizations into flatter, more democratic designs. Research gap – The current research is extensive but focuses mainly on systems and procedures, with little attention to how these changes affect middle managers and how they perceive them. Research question - How do middle managers perceive and respond to power changes during democratizing transformation in traditionally managed organizations? Objectives - This dissertation aims to better understand the power changes associated with organizational democratization through middle managers’ interpretations and responses and related consequences. Furthermore, the dissertation seeks to understand the nature of middle managers' resistance to or acceptance of the change and to identify opportunities for optimizing the transformation process. Methods - The dissertation is based on empirical research into middle managers' lived experiences within large, traditional, regulated companies, utilizing a qualitative phenomenological approach. The primary data collection method included in-depth semi-structured interviews with 18 middle management representatives who transitioned from traditional to more autonomous forms of organizing due to democratizing transformation. The interviews with respondents were conducted in several iterations during the ongoing organizational changes over a period of one and a half years in two major corporations. The data were analysed using Interpretative Phenomenological Analysis (IPA) with an idiographic approach (within-case then cross-case) and a double-hermeneutic stance. The Foucauldian concept of power framed interpretation.